Isolation and identification of phenolic compounds in Chinese purple yam and evaluation of antioxidant activity. (October 2018) - Zhang, Junhong; Tian, Honglei; Zhan, Ping; Du, Fangling; Zong, Aizhen; Xu, Tongcheng
Abstract: Purple yam ( Dioscorea alata L ) has been extensively investigated in the fields of biomedicine, pharmacology, and toxicology. As functional components, phenolic compounds exhibit high levels of biological activities. In this study, seven phenolic compounds extracted from Chinese purple yam were successfully identified using high-performance liquid chromatography combined with high-resolution electrospray ionization mass spectrometry. Comparison of the retention time and mass spectra of the extracted compounds with those of authentic standards confirmed the existence of ferulic acid (4 ) and sinapic acid (5 ). And five kinds of the previously unidentified phenolic compounds were revealed, including one kind of dihydroxybenzoic acid (vanillic acid, 2 ), two sets of hydroxycinnamic acids (caffeic acid, 1 and p -coumaric acid, 3 ), and two kinds of anthocyanins (quercetin dehydrate, 6 and kaempferol, 7 ). In addition, the total antioxidant activity and DPPH free radical scavenging activity of the isolated fractions were evaluated, and the concentrated F1 fraction displayed a high total antioxidant activity (2.38 mM) and DPPH free radical scavenging activity (89.56%). This study provided an in-depth insight into the diversified components and antioxidant activity of purple yam. Such information is beneficial to the post processing and storage of purple yam products. Graphical abstract: Image 1 Highlights: Three fractions of phenolic compound mixtures were isolated from Chinese purple yam. F1 fraction exhibited a higher total antioxidant activity and DPPH free radical scavenging activity than F2 or F3 fraction. HPLC and high-resolution ESI–MS worked well to identify seven phenolic compounds. Quercetin dehydrate and kaempferol were confirmed. This work indicated the potential importance of purple yam extracts on biological activity and human health.